PENGARUH LOKASI, HARGA, KELENGKAPAN PRODUK DAN DISPLAY LAYOUT TERHADAP KEPUASAN KONSUMEN PADA TOKO GROSIR WIJAYA KECAMATAN KERTOSONO KABUPATEN NGANJUK - Ali Mauludi; Alfina Medytarisa (Bajang Institute, 2023)
There are many retail businesses that can be found in urban or rural areas such as shops. So this business has experienced rapid development from year to year and has a high level of competition. Store business needs to develop the right marketing strategy in order to attract consumer interest to realize consumer satisfaction. Consumer satisfaction directly or indirectly will have an impact on bussiness succesness. This study aims to determine the effect of location, price, product completeness and display layout on customer satisfaction at the Wijaya grocery store, Kertosono District, Nganjuk Regency partially and simultaneously using an associative quantitative approach. The data source used is primary data by distributing questionnaires to 50 respondents who have purchased at the Wijaya grocery store, Kertosono District, Nganjuk Regency. The results showed that price, product completeness and display layout partially affected customer satisfaction, while location partially had a positive but not significant effect on customer satisfaction at the Wijaya Kertosono wholesale store. Meanwhile, location, price, product completeness and display layout simultaneously have a positive effect on consumer satisfaction at the Wijaya grocery store, Kertosono District, Nganjuk Regency, with a total effect of 65%.